Neuroinflammation and major depressive disorder: astrocytes at the crossroads - Puentes-Orozco, Melissa; Albarracin, Sonia L.; Velásquez, María Marcela (Frontiers in Cellular Neuroscience, 2024)
Major depressive disorder is a complex and multifactorial condition, increasingly linked to neuroinflammation and astrocytic dysfunction. Astrocytes, along with other glial cells, beyond their classic functions in maintaining brain homeostasis, play a crucial role in regulating neuroinflammation and neuroplasticity, key processes in the pathophysiology of depression. This mini-review explores the involvement of astrocytes in depression emphasizing their mediation in neuroinflammation processes, the impact of astrocytic dysfunction on neuroplasticity, and the effect of some antidepressants on astrocyte reactivity. Recent evidence suggests that targeting astrocyte-related signaling pathways, particularly the balance between different astrocytic phenotypes, could offer promising evidence for therapeutic strategies for affective disorders. Therefore, a deeper understanding of astrocyte biology may open the way to innovative treatments aimed at mitigating depressive symptoms by impacting both neuroinflammation and imbalances in neuroplasticity.